LANGUAGE ACQUISITION USED BY AUTISTIC CHILD IN THE INCLUSSION KINDERGARTEN OF NAMIRA SCHOOL - Sugeng Edy Mulyono; Ayu Mayang Dini (Program Studi Bahasa Inggris, Universitas Panca Marga, 2022)
The research describe the the language acquisition used by Autistic Children the Inclussion Kindergarten of Namira School. In the practice, psycholingistics always applies the lingiuistics and psychology knowledge in analysing some problems such as language leraning and social problems which is related to language. Abdul Chaer (2009). The research uses Bagdon and Biklen method for the data analysis which is decided into three main techniques, they are 1) Data Reduction, 2) Displaying Data, 3) Data Verification and Conclusion (Bagdon, R.C., and Biklen, S. K. 1998). The results of this research concludes that The autistic child is excited to listen, understand, and respond some question well in the interaction when he gets the greeting at first before the learning is held. Not all of sentences can be spoken by right pronunciation, some pronunciation felt difficult. The autistic child sometimes does not focus in the learning because of not in good mood and it can influences the next interaction. The autistic child focuses in the main point of the interaction when the teacher has some materials which is in concreted form and can be looked or touched by the autistic child. The autistic child can listens, understands, and responds well if the sentence question is spoken repeatedly near the autistic child